(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the historical development of compositional structures in the landscape genre, exploring their evolution from classical artistic traditions to contemporary creative directions. The study scientifically explains the strict compositional framework formed in ancient and Renaissance landscapes, the spatial construction principles of Romanticism and Realism in the 18th–19th centuries, and the new interpretation of the compositional center through light and atmosphere in Impressionism. It also examines the emergence of abstract, conceptual, and experimental directions in contemporary landscape art, highlighting the reinterpretation of compositional concepts enriched with visual rhythm, color fields, minimalism, and photographic approaches. Research results show that the evolution of landscape composition is not only a formal transformation but also a deep shift in artistic worldview, perception, and expressive means throughout history.